Numerical investigation of the fluid retention in the tank with a horizontal negatively buoyant jet. (February 2023) - Chi, Xiangyu; Dong, Pengfei; Wang, Naihua
Abstract: The fluid retention in the volume control tank (VCT) will delay the boric concentration of the Reactor Coolant System (RCS) during the boration process in the nuclear power plant. In this work, we studied the fluid retention in the tank with a horizontal negatively buoyant jet employing an experimentally validated computational fluid dynamics (CFD) model. The effects of concentration difference, inlet volume flow rate, nozzle diameter, and Richardson number ( Ri ) on fluid retention are analyzed to provide insights into the design and operation of VCT and other similar industrial equipment. The results show that there are two typical mixing patterns in the tank, the stratified pattern and the unstratified pattern. A criterion is provided to distinguish the mixing pattern. Increasing the concentration difference/nozzle diameter and decreasing the inlet volume flow can suppress the mixing process inside the tank and consequently weaken fluid retention. The variation of the fluid retention with the Ri is divided into three regimes by two critical numbers. The fluid retention is almost insensitive to the Ri when the number is inferior to the first critical number or exceeds the second critical number. Otherwise, the rise of the Ri inhibits fluid retention. Hence, the Ri is recommended to be maintained above the second critical value to minimize fluid retention in practice. Highlights: The fluid retention in the horizontal negatively buoyant jet tank is analyzed. A stratification criterion for the tank is provided. Enlarging concentration differences or reducing flow rates weaken fluid retention. The larger the nozzle diameter, the weaker the fluid retention. Ri should be maintained above the second critical value to minimize retention.